Collection of Ulli and Georgina Beier (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Pottery; Books; Art Collection; Yoruba Art; Yoruba Pottery